Motivasi Belajar Dan Faktor-Faktor Yang Mempengaruhi Siswa Kelas XI SMA N 3 Brebes - Gunarto, Yuhdan Arief Putra Pratama (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
Research on Learning Motivation and Influencing Factors in Class XI Science Students of SMA N 3 Brebes behind by students unable to add enthusiasm in learning activities, not liking certain lessons caused by too many teachers, students not asking the teacher, students often working on homework (PR) at school, lack of knowledge about how to learn and assume that learning is less fun compared to smartphone toys and applications contained on smartphones as well as the applications in them and the applicable curriculum..This type of research is a quantitative research with a survey research design. The population in this study amounted to 180 students, including XI IPA 1, XI IPA 2, XI IPA 3, XI IPA 4, XI IPA 5.The sampling technique in this study used a cluster random sampling technique. that is, grouping individuals or clusters from the population that is taken after that checks the group of individuals or clusters from the population that is taken after that randomizes the eligible groups. The sample in this study was 2 classes, namely XI IPA 2 AND XI IPA 5. Based on the type of survey research, it can be said that students' learning motivation is at a moderate level so that it can be said to have no significant effect on the learning motivation of students in science class at SMAN 3 Brebes.